Traditional Games on Increasing Arm and Leg Muscle Strength in Deaf Students - Arimbi, Arimbi (Department of Physical Education, Sport, Health and Recreation, 2022)
The purpose of this study was to find out how effect of the traditional tug of war game on increasing the arm and leg muscle strength of students with special needs for the deaf. The tug of war game is one of the traditional games that is very popular among the people. This traditional game was chosen because in several references it is known that this game can affect the strength of the hand and leg muscles, as it is known that children with special needs or disabilities have difficulty active movement as a result of the inability of some of their body muscles, one of the most common conditions is weakness in the muscles of the legs. Children with hearing impairment also have the right to receive proper teaching so that their development and growth can run well, especially their movement or psychomotor development. This research will involve all deaf students at SLB-B YPPLB Cendrawasih Makassar, which lasts for 4 weeks with two measurements at the beginning and end of the study. The research method used is one group pre post test. Measurement of arm muscle strength using a hand dynamometer and leg muscle strength measurement using a leg dynamometer with an accuracy of up to 0.5 cm. The results showed that there was a change in arm muscle strength where the average increased after tug of war training with an average of 25.28 kg (7.34) increased to 29.94 kg (8.28) with a change of 4.66 kg and changes in leg muscle strength after routine tug of war, where the average experienced the increase after tug of war with an average of 28.23 kg (8.57) increased to 34.35 kg (8.17) with a change of 6.12 kg. The conclusion of this study is that the traditional tug of war game which is applied for 4 weeks has an effect on increasing the strength of the arm and leg muscles of deaf students.